Распространение тетранихоидных клещей и зоны их наибольшей вредоносности на Украине - Акимов, И.А.; Войтенко, А.Н.; Погребняк, С.Г. (Вестник зоологии, 1993)
Peculiarities of principal orchard mite destribution is considered. Changes in the role of different injurious mite species in the orchards are discussed.